(untitled) (Bangladesh Journal of Child Health, 2020)
Down syndrome is the most common genetic disorder among live born infants, which is associated with a number of congenital malformations and requires a huge medical and social cost. Here, we report a very rare association in an infant with Down syndrome and XY disorder of sex development (DSD). Bangladesh J Child Health 2020; VOL 44 (1) :48-51